Heterostemma menghaiense (Apocynaceae), a new record for Laos and Thailand - Thammarong, Woranart; Rakarcha, Sarayut; Pongamornkul, Wittaya; Rodda, Michele (Thai Forest Bulletin (Botany), 2021)
Heterostemma menghaiense is reported as a new record for the flora of Laos and Thailand. A description based on Thai and Lao collections, photographs and notes are provided.